Structural behaviour of singly reinforced OPS beams - Mohammad, Abdul Mannan; Teo, Delsye Ching Lee; Kurian, V. J. (2006)
Concrete using oil palm shell (OPS) as coarse aggregate has been found useful as lightweight concrete and strengths of up to 28 MPa have been attained. To further investigate its suitability for structural purposes, additional tests are required. Therefore, this paper presents an experimental investigation on the modulus of elasticity and flexural behaviour of three reinforced OPS concrete beams with different effective depths and reinforcement ratios. From the investigation, OPS concrete show promising results for use as structural members, especially for the construction of low cost houses in areas where oil palm is found in abundance.